Validation of a fast UPLC–MS/MS method for quantitative analysis of opioids, cocaine, amphetamines (and their derivatives) in human whole blood. (October 2015) - Feliu, Catherine; Millart, Hervé; Guillemin, Hélène; Vautier, Damien; Binet, Laurent; Fouley, Aurelie; Djerada, Zoubir
Background: Conventional methods for analysis of drugs of abuse require multiple assays which can be both expensive and time-consuming. This work describes a novel, rapid, simple and sensitive method for the quantification of 14 illicit drugs and their metabolites in whole blood.Results/methodology: This method employed a rapid liquid–liquid sample extraction of whole blood followed by UPLC–MS/MS analysis. Calibration curves were validated for analysis of appropriate concentrations. Inter- and intra-assay variations were <14.8%. Deviation of accuracy was <14.9% from target concentration for each quality control level.Conclusion: This work described the development and the full validation of a precise, sensitive and accurate assay. After validation, this new assay was successfully applied to routine toxicological analysis.